2018
DOI: 10.1111/maps.13106
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopy of shocked enstatite‐rich meteorites

Abstract: We present Raman patterns of enstatite in different classes of enstatite‐rich chondrites and achondrites of various shock levels as previously reported from petrographic observations and X‐ray diffraction analyses. Thin sections or mineral separates of four enstatite chondrites (LaPaz Icefield [LAP] 02225, MacAlpine Hills [MAC] 02837, Pecora Escarpment [PCA] 91020, and Itqiy), three aubrites (Larkman Nunatak [LAR] 04316, Khor Temiki, and Allan Hills [ALH] 84008), and a ureilite (Sayh al Uhaymir [SaU] 559) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Wang et al, , , ). These were not tracked as a function of pressure owing to their greater resistance to shock at the pressures examined here (e.g., Farrell‐Turner et al, ; Harriss & Burchell, ; Johnson et al, ; Zhang et al, ). The broad humps near 1,000 cm −1 may also vary with composition (Al–O to Si–O ratios) in plagioclase glass or maskelynite (e.g., Fritz et al, ).…”
Section: Methodsmentioning
confidence: 96%
“…Wang et al, , , ). These were not tracked as a function of pressure owing to their greater resistance to shock at the pressures examined here (e.g., Farrell‐Turner et al, ; Harriss & Burchell, ; Johnson et al, ; Zhang et al, ). The broad humps near 1,000 cm −1 may also vary with composition (Al–O to Si–O ratios) in plagioclase glass or maskelynite (e.g., Fritz et al, ).…”
Section: Methodsmentioning
confidence: 96%
“…In our data, peak position shifts of the most intense peaks can be observed down to a few cm −1 , explained by the variation of the structural cations, as described in depth by Huang et al 39 Finally, Raman investigation of various pyroxenes in the breccia confirmed the absence of any shock‐induced transformation of pyroxene, in agreement with the literature. Modification by high‐pressure processes should be visible in Raman spectra through significant peak broadening or the occurrence of amorphous glass 44,45 which is not observed in our spectra. However, Leroux et al 46 observed some local shock microstructures inside pyroxenes at the nanoscale with TEM microscopy, which may be too small and/or scarce to be detected at the Raman scale of observation.…”
Section: Resultsmentioning
confidence: 72%
“…Existence of enstatite in AAT-1 was also determined by its characteristic peaks (Figure 6) observed for Si-O-Si stretching at 665 cm À1 , Si-O-Si stretching at 687 cm À1 , Si-O stretching at 1014 cm À1 , and 1034 cm À1 . 34 The peaks at $106-300 cm À1 regions obtained in the sample mapping analysis and most of the single spectra (Figure 7) are most closely matched with titanium oxide minerals. It is known that titanium oxide minerals, which are found in three types of crystalline 35 Anatase converts into rutile at high temperatures and pressures.…”
Section: Raman Spectroscopymentioning
confidence: 71%
“…S, represented by yellow color in the image, displays a collective structure in coarse‐grained pyroxene. This structure can be associated with a troilite‐orthopyroxene ingrowth in diogenites 34 . However, an increase in Ti is observed towards the sample edge (Figure 9C area).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation